Student nurses' perception of the clinical midwifery experience as a learning environment - R. Dürrheim (AOSIS, 1993)
The student nurse may have a different perception of her learning environment from that which the instructor intended. The purpose of the study was to determine the perception of student nurses of clinical midwifery experience as a teaming milieu. Student nurses in their third and fourth year at a nursing college in Transvaal were involved in the research. A literature study regarding factors that can influence clinical learning of student nurses in the midwifery units was done. Questionaires were used to collect data regarding personal information, the learning environment, and problems regarding clinical skills. Data were analysed by means of a SAS computer programme.